2016
DOI: 10.1002/2016gl071104
|View full text |Cite
|
Sign up to set email alerts
|

Regional and stress drop effects on aftershock productivity of large megathrust earthquakes

Abstract: The total number of aftershocks increases with main shock magnitude, resulting in an overall well‐defined relationship. Observed variations from this trend prompt questions regarding influences of regional environment and individual main shock rupture characteristics. We investigate how aftershock productivity varies regionally and with main shock source parameters for large (Mw ≥ 7.0) circum‐Pacific megathrust earthquakes within the past 25 years, drawing on extant finite‐fault rupture models. Aftershock prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…High stress drop ruptures drive more elevated stresses at the periphery of the fault that may contribute to higher aftershock productivity; however, this effect might be reversed by the size of the rupture that is smaller for a higher stress drop. Our observations indicate that the geometric compactness that results from high stress drop dominates: a smaller volumetric activation from high stress drop ruptures results in fewer triggered aftershocks (Wetzler et al, ).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…High stress drop ruptures drive more elevated stresses at the periphery of the fault that may contribute to higher aftershock productivity; however, this effect might be reversed by the size of the rupture that is smaller for a higher stress drop. Our observations indicate that the geometric compactness that results from high stress drop dominates: a smaller volumetric activation from high stress drop ruptures results in fewer triggered aftershocks (Wetzler et al, ).…”
Section: Discussionmentioning
confidence: 62%
“…The opposite relationship was documented for recent (1990–2016) major megathrust ruptures ( MW7.0) (Wetzler et al, ), suggesting that high stress drop corresponds to a smaller rupture area and therefore fewer aftershocks. This is supported by a tendency for megathrust aftershocks to occur on the periphery of large‐slip zones (Wetzler et al, ; Van Der Elst & Shaw, ). Earthquakes rupturing at supershear velocities also appear to have low aftershock productivity (Bouchon & Karabulut, ).…”
Section: Introductionmentioning
confidence: 89%
“…Likewise, Shearer et al () found low stress drops in regions of high slip bracketed by higher stress drop events on some segments of the complex 1992 M 7.3 Landers, CA, earthquake. A correlation between high stress drop main shocks and lower aftershock productivity was also found for global subduction zone earthquakes (Wetzler et al, ). Ross et al () attributed an aftershock deficit in the vicinity of the M 5.2 Borrego Springs, CA, earthquake to complete stress drop (~80 MPa).…”
Section: Source Parameter Results and Discussionmentioning
confidence: 95%
“…The 2014 Iquique earthquake produced many aftershocks, but the aftershocks had low b values, despite the occurrence of a large aftershock (Hayes et al, 2014b). There is a weak tendency for high-stress-drop megathrust ruptures with a given moment to have lower aftershock production, which is attributed to the smaller main-shock rupture dimensions (Wetzler et al, 2016). The source dimensions of the main slip zone for the 2014 Iquique event were indeed unusually small for a great earthquake.…”
Section: Aftershock Distributionmentioning
confidence: 96%
“…Peru and Marianas produced the fewest megathrust events in this time period, at ~0.09 and 0.08 events/km, respectively. The regional differences in seismic productivity are also manifested in large event aftershock productivity, with lower values found in Mexico-Middle America, Peru, and Chile and higher values found in Tonga, Sumatra, Japan, and Southwest Pacific island arcs (e.g., Singh and Suárez, 1988;Wetzler et al, 2016). In general, island-arc megathrusts that host great earthquakes tend to be more productive than continental arcs.…”
Section: Regional Seismic Productivitymentioning
confidence: 99%